Toward More Effective Public Health Interventions during the COVID-19 Pandemic: Suggesting Audience Segmentation Based on Social and Media Resources. Issue 1 (2nd January 2021) - Ihm, Jennifer; Lee, Chul-Joo
ABSTRACT: In response to the COVID-19 pandemic, public health communication campaigns have been targeted at reducing viral transmission, specifically among populations most vulnerable to infection and death from the virus (e.g. older adults). However, other individuals who have not been defined as vulnerable populations may also suffer from a decrease in health because of the measures aimed at reducing viral transmission, such as social distancing. To illuminate this issue, we investigate the role of social and media resources in complementing limited offline communication and supporting mental and physical health during this pandemic. We then suggest an alternative audience segmentation strategy based on social and media resources for public health interventions. Based on online survey data from 723 adults in South Korea, the regression analysis results indicated that individuals with lower levels of social resources suffered more during the pandemic. The cluster analysis results revealed that, contrary to the traditional definition of vulnerable populations, a cluster of younger people were unhealthier than a cluster of older people because of a lack of social resources. Clusters with different levels of ICT skills and uses for health-related activities also experienced the pandemic differently. These findings imply public health interventions should focus on social resources beyond the demographic factors to determine target audiences, and that they should take advantage of the target audiences' media resources to encourage them to forge intimate connections with others and to engage in health-related activities.